Refletindo sobre o papel do professor alfabetizador na perspectiva da escola bilíngue - Pereira, Juleide Catarina da Silva (2012)
The research object of this paper is to show the possibilities of knowing the process of developing a proposal for a literacy, with emphasis on learning and inclusion the these school bilingual in the literacy class. Front of this reality, the school with their teachers, should think of literacy as a dynamic process expand the universe of knowledge offering various forms of learning without disregarding their age and the influence of technological means for learning bilingual.